(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Relevance of the topic. The incidence of kidney pathologies in countries around the world is increasing every year. These figures are slightly higher in Central Asian countries. The reason depends on the lifestyle of the population, climate, drinking water and many other factors. This, in turn, leads to an increase in the number of women who undergo pregnancy without kidney pathology. Fetuses with kidney pathology in mothers do not affect the organs of the urinary system, including the morphological development of the bladder. Analysis of morphometric changes during the development of the bladder in fetuses without kidney pathology and mothers with kidney pathology at different stages of gestation. Purpose of the study. Identification of morphological changes in the bladder in fetuses with kidney pathology in their mothers.